2017
DOI: 10.1016/j.cobeha.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The pre/parasubiculum: a hippocampal hub for scene-based cognition?

Abstract: HighlightsWe consider internal representations of the world in the form of scenes.The anterior medial hippocampus is implicated in scene-based cognition.This region contains the pre/parasubiculum.The pre/parasubiculum is a primary target of a major visuospatial processing system.The pre/parasubiculum may be the hippocampal hub of the scene processing network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
81
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 62 publications
12
81
0
Order By: Relevance
“…Navigation is typically associated with the posterior hippocampus (Maguire et al, 2000), while scene construction, autobiographical memory and future thinking are more often associated with the anterior hippocampus (Dalton & Maguire, 2017;Maguire & Mullally, 2013;Zeidman & Maguire, 2016). Understanding the specialisation of different regions of the hippocampus will also be an important topic for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Navigation is typically associated with the posterior hippocampus (Maguire et al, 2000), while scene construction, autobiographical memory and future thinking are more often associated with the anterior hippocampus (Dalton & Maguire, 2017;Maguire & Mullally, 2013;Zeidman & Maguire, 2016). Understanding the specialisation of different regions of the hippocampus will also be an important topic for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Observed 614 coherence with the parahippocampal cortex during scene imagination is consistent with the 615 parahippocampal cortex's proposed role in processing scenes(Epstein, 2008; Mullally and Maguire, 616 2011). This connectivity profile, therefore, suggests that the anterior hippocampus may be a 617 convergence zone for appropriate object categories and their interaction within a defined space, 618 permitting the generation of scene imagery(Dalton and Maguire, 2017).619 620 In summary, our results characterise, for the first time, a core neural dynamic which underlies scene 621 construction, a process held by some to be fundamental to key cognitive functions including episodic 622 memory and future-thinking. Previous studies have demonstrated co-activation of (Hassabis et al, 623 2007b), and a dependency on (Hassabis et al, 2007a; Bertossi et al, 2016a), the hippocampus and 624 vmPFC during scene construction.…”
mentioning
confidence: 81%
“…The subiculum plays an important role in spatial processing and navigation (Boccara et al, 2010;Dalton & Maguire, 2017;Hodgetts et al, 2017;Lever et al, 2009;Taube et al, 1990), so we expected it to be modulated by spatial attention (e.g., Aly & Turk-Browne, 2016a, 2016b.…”
Section: Introductionmentioning
confidence: 99%